Selling Honey and Making Money: An Instagram Marketing Strategy and Basic Photography Training for Women of Kemlagi Village, Mojokerto, East Java - Rahmawati, Aulia; Tutiasri, Ririn Puspita; Febriana, Poppy; Febriyanti, Syafrida N. (Indonesian Community Empowerment Journal, 2023)
Kemlagi village is one of honey-producing village in Mojokerto, East Java, that has not been paid much attention to by the local government, both in terms of potential and marketing strategy. The involvement of housewives in the marketing sector of the Kemlagi village honey business has not been seen. This community service aims to increase women's empowerment in the social media marketing sector so that business development and community income occur. This community service has two focus activities, namely Instagram marketing training and basic photography training. The presenters of this event were a team from the Communication Science study program of the Universitas Pembangunan Nasional (UPN) "Veteran" and the Universitas Muhammadiyah Sidoarjo. The target participants for this event are women in Kemlagi village, Mojokerto who run a business selling honey and its products. A total of 30 mothers participated in this training event. The training event consisted of opening, opening remarks, Instagram marketing and basic photography materials, questions and answers and closing. After the event, an evaluation of the benefits and participants' understanding of this training material was carried out. The long-term goal of this training is that the home business of the Kemlagi village is getting more advanced and its potential is getting more and more optimized. It is hoped that this home business will develop so that in the future Kemlagi village can develop into a honey edutourism area in East Java.